Granulocyte colony‐stimulating factor improves neuron survival in experimental spinal cord injury by regulating nucleophosmin‐1 expression. Issue 6 (7th February 2014) - Guo, Yuji; Liu, Shangming; Wang, Ping; Zhang, Hui; Wang, Fuwu; Bing, Lujun; Gao, Jiangang; Yang, Jie; Hao, Aijun
<x xml:space="preserve">Abstract</x> Granulocyte colony‐stimulating factor (G‐CSF) and its related mechanisms were investigated to assess the potential for this factor to exert neuroprotective effects against spinal cord injury in mice. Recombinant human granulocyte colony‐stimulating factor (rhG‐CSF) was injected into mice spinal cord hemisection models. Locomotor activity was assessed by using the Basso‐Bettie‐Bresnahan scale. Neurons isolated from spinal cords were cultured in vitro and used in a neuronal mechanical injury model. Three treatment groups were compared with this model, 1) G‐CSF, 2) G‐CSF + NSC348884 (a nucleophosmin 1‐specific inhibitor), and 3) NSC348884. Immunofluorescence staining and Western blotting were performed to analyze the expression of G‐CSF and nucleophosmin 1 (Npm1). TUNEL staining was performed to analyze apoptosis after G‐CSF treatment. We found that the G‐CSF receptor (G‐CSFR) and Npm1 were expressed in neurons and that Npm1 expression was induced after G‐CSF treatment. G‐CSF inhibited neuronal apoptosis. NSC348884 induced p53‐dependent cell apoptosis and partially blocked the neuroprotective activity of G‐CSF on neurons in vitro. G‐CSF promoted locomotor recovery and demonstrated neuroprotective effects in an acute spinal cord injury model. The mechanism of G‐CSF's neuroprotection may be related in part to attenuating neuronal apoptosis by NPM1. © 2014 Wiley Periodicals, Inc.